Children’s perspectives on the relations between home and school - Markström, Ann-Marie (International Journal about Parents in Education, 2023)
The aim of the article is to shed light on children’s perspectives of the relations between home and school. The study is based on 52 interviews with children aged 12-13 years in Sweden about their knowledge and notions of the relations between their parents and teachers, and what they perceive their own role to be in this context. The study reveals that the children’s understandings are drawing on both ideas of connectedness and autonomy to different actors characterised by a vertical or horizontal frame and that generational and institutional power are important in their understanding of the relations. The results reveals the different ways in which children talk about home-school relations, namely as (1) an asymmetric vertical “keep-apart-relation” characterised by institutional power, generational power and children’s autonomy and power and (2) a horizontal relation that is characterised by a symmetric power relation between the actors, i.e. they think that the parties to some extent sometimes have an equal influence in the relation. In addition, the study indicates that children adopt different strategies in relation to the adults. The children’s accounts show that they reproduce and also resist the social order and structure.